2010
DOI: 10.1038/embor.2010.49
|View full text |Cite
|
Sign up to set email alerts
|

Imbalances in p97 co‐factor interactions in human proteinopathy

Abstract: The ubiquitin-selective chaperone p97 is involved in major proteolytic pathways of eukaryotic cells and has been implicated in several human proteinopathies. Moreover, mutations in p97 cause the disorder inclusion body myopathy with Paget disease of bone and frontotemporal dementia (IBMPFD). The molecular basis underlying impaired degradation and pathological aggregation of ubiquitinated proteins in IBMPFD is unknown. Here, we identify perturbed co-factor binding as a common defect of IBMPFDcausing mutant p97.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 29 publications
5
118
1
Order By: Relevance
“…Although some reports have shown that pathogenic mutants have ATPase activities similar to that of the wild type (6,21), others have demonstrated significantly enhanced ATPase activity (19,20,22). No mechanistic interpretation has been offered in the latter reports as to why the ATPase activity is elevated.…”
Section: Data Collectionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although some reports have shown that pathogenic mutants have ATPase activities similar to that of the wild type (6,21), others have demonstrated significantly enhanced ATPase activity (19,20,22). No mechanistic interpretation has been offered in the latter reports as to why the ATPase activity is elevated.…”
Section: Data Collectionmentioning
confidence: 58%
“…It is conceivable that such deviations in the nucleotide-binding properties of mutant p97 may also be reflected in their ATPase activities. However, conflicting observations have been reported showing that the pathogenic p97 mutants have either similar (6,21) or higher (19,20,22) ATPase activities compared with the wild type.…”
mentioning
confidence: 91%
“…Due to an altered inter-subunit communication in IBMPFD mutants the D1 domains fail to regulate their respective nucleotide-binding states as evidenced by a lower amount of pre-bound ADP and weaker affinity for ADP, resulting in a better accessibility for ATP in comparison to the wild-type protein [29,30]. The altered conformational equilibrium of the N domain in p97 disease mutants is accompanied by elevated ATPase activities in vitro [43,115,116] and altered interactions with some but not all cofactors in cells, which has been proposed to be key to the pathogenesis of IBMPFD [10,[116][117][118] (for a recent review see [119]). Specifically, increased amounts of p47, UFD1-NPL4, and ataxin-3, but decreased amounts of UBXD1 and UBE4B have been found.…”
Section: Nucleotide-dependent Control Of Cofactor Interactionsmentioning
confidence: 99%
“…Two reports showed that mutants exhibit higher ATPase activity than the wild type to various degrees (Manno et al, 2010;Weihl et al, 2006). One paper, by contrast, reported no significant alterations in ATPase activity of four IBMPFD mutants (Fernandez-Saiz and Buchberger, 2010). Mutant p97 also displayed an even higher level of heat-stimulated ATPase activity (Halawani et al, 2009).…”
Section: Nucleotide-binding Affinity and Atpase Activitymentioning
confidence: 99%